Znaczenie postaci św. Jana Kapistrana w procesie kształtowania tożsamości wrocławskiego konwentu Franciszkanów Reformatów - Musiał, Marcin (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The objective of the present study is to examine the role of St. John of Capistrano – a Franciscan preacher and missionary – in the process of forming the identity of the community of Czech Reformed Franciscans in the 17th century. The aforementioned figure was the actual initiator of the creation of Czech Observant province, which in the 17th century was transformed into a Reformed province. Based on the analysis of the description of history of the convent of St. Anthony in Wrocław, included in Chronica de origine(1678) by Father Bernard Sannig, and of the painting St. John of Capistrano from this convent, it becomes possible to present this saint as an important element of the identity,both on the provincial and local (the convent in Wrocław) level
Keywords: Wrocław